PENGARUH FAKTOR TINGKAT SUKU BUNGA, DEBT TO EQUITY RATIO DAN TINGKAT INFLASI TERHADAP YIELD TO MATURITY OBLIGASI KORPORASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Megawati Megawati (Jurnal Praktik Bisnis, 2015)
This research aimed to analyze the influence of interest rate, debt to equity ratio and the inflation rate to the yield to maturity of corporate bonds. Population of this research is all corporate bonds listed on the Indonesia Stock Exchange in 2009-2013. The research sample is determined by purposive sampling consisting of 65 samples. The analytical method used is structural equation modeling (SEM). This study shows that there is a positive and significant relationship between the interest rate on the yield to maturity of corporate bonds, debt to equity ratio and significant positive effect on the yield to maturity of corporate bonds and the rate of inflation and significant positive effect on the yield to maturity of corporate bonds. Keywords: interest rate, debt to equity ratio, inflation rate yield to maturity